Composition and textural properties of soot and study of their oxidative elimination by catalytic process. (24th September 2009) - Courcot, D.; Laversin, H.; Ledoux, F.; Cazier, F.; Matta, J.; Cousin, R.; Aboukais, A.
Diesel soot and reference carbon black samples have been characterised by analysis of the organic compounds fraction and determination of textural characteristics (specific area). The potential to eliminate such carbonaceous particles has been investigated using a Cu/ZrO2 solid catalyst promoted by potassium additives. The reactivity of soot samples depends on the organic compounds content. In general, Cu-K/ZrO2 catalyst is able to lower significantly the soot oxidation temperature of almost 200°. This high activity is related to the ability of potassium to interact with copper species and to favour the release of active oxygen from the catalyst.